2009
DOI: 10.1111/j.1467-9280.2009.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Improves and Impairs Early Vision

Abstract: Recent studies indicate that emotion enhances early vision, but the generality of this finding remains unknown. Do the benefits of emotion extend to all basic aspects of vision, or are they limited in scope? Our results show that the brief presentation of a fearful face, compared with a neutral face, enhances sensitivity for the orientation of subsequently presented low-spatial-frequency stimuli, but diminishes orientation sensitivity for high-spatial-frequency stimuli. This is the first demonstration that emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
195
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(234 citation statements)
references
References 30 publications
17
195
6
Order By: Relevance
“…3 Recent evidence suggesting that negative images precipitate a shift in the balance between the magnocellular and parvocellular channels, favoring the magnocellular (Bocanegra & Zeelenberg, 2009) provides one potential mechanism for the slower identification of negative images. The magnocellular pathway is the primary input to the dorsal processing stream (DeYoe & Van Essen, 1988;Maunsell, Nealey, & DePriest, 1990) that is involved in spatial perception and perception for action (Goodale & Milner, 1992), but does not support the conscious recognition of objects (Mishkin, Ungerleider, & Macko, 1983;Ungerleider & Haxby, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Recent evidence suggesting that negative images precipitate a shift in the balance between the magnocellular and parvocellular channels, favoring the magnocellular (Bocanegra & Zeelenberg, 2009) provides one potential mechanism for the slower identification of negative images. The magnocellular pathway is the primary input to the dorsal processing stream (DeYoe & Van Essen, 1988;Maunsell, Nealey, & DePriest, 1990) that is involved in spatial perception and perception for action (Goodale & Milner, 1992), but does not support the conscious recognition of objects (Mishkin, Ungerleider, & Macko, 1983;Ungerleider & Haxby, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although this finding suggests that emotional stimuli can increase visual sensitivity, the time course of such an improvement was not assessed. In addition, subsequent research (Bocanegra & Zeelenberg, 2009) found that the detection benefit reported by Phelps et al occurs only for low spatial frequency gratings. For high spatial frequency gratings there was, instead, a cost associated with a fearful precue.…”
mentioning
confidence: 99%
“…To test these hypotheses, I used a modified version of a task used in previous research (Bocanegra & Zeelenberg, 2009b;Borst & Kosslyn, 2010b;Nicol, Perrotta, Caliciuri, & Wachowiak, 2013b). Specifically, participants detected a tilted HSF Gabor patch that appeared after the brief presentation of a facial expression.…”
Section: Current Researchmentioning
confidence: 99%
“…In fact, neuroimaging studies have demonstrated that emotional pictures elicit more activation in the early visual areas (such as V1) than do neutral pictures (e.g., Lang et al, 1998;Morris et al, 1998;Vuilleumier, Richardson, Armony, Driver & Dolan, 2004). In addition, two studies converge in demonstrating that fearful faces enhance contrast sensitivity (Phelps, Ling & Carrasco, 2006) and orientation sensitivity of low spatial frequency Gabor patches (Bocanegra & Zeelenberg, 2009). The amygdala is presumably at the root of this effect: At an early stage, the emotional valence of the stimulus is processed by the amygdala which --through backward projections to early visual areas --modulates subsequent low-level perceptual processing (Vuilleumier, 2005).…”
mentioning
confidence: 99%